Fabrication of Alumino-Silicate-Fluoride based bioglass derived from waste clam shell and soda lime silica glasses - Abdul Rahman, Nadia Asyikin; Matori, Khamirul Amin; Mohd Zaid, Mohd Hafiz; Zainuddin, Norhazlin; Abd. Aziz, Sidek; Ahmad Khiri, Mohammad Zulhasif; Abdul Jalil, Rohaniah; Wan Jusoh, Wan Nurshamimi (Elsevier, 2019)
Through the traditional approach of the melt-water quenching technique, it is seen that Alumino-Silicate-Fluoride (ASF) bioglass system is assembled. Through the very investigation of this paper, it is noted that preparation of ASF bioglass is composed of Clam Shells (CS), Soda Lime Silicate (SLS), CaF2, P2O5, and Al2O3 with the empirical formula [xCS⋅(45 − x)SLS⋅15CaF2⋅20P2O5⋅20Al2O3] where x= 5, 10, 15 and 20 (wt%). The waste materials used to produce ASF bioglass were CS and SLS. The physical and structural properties of bioglass are obtained through Energy X-ray (EDX), density (ρ), molar volume (Vm), X-ray diffraction (XRD), Fourier Transform Infrared (FTIR) and Field Emission Scanning Electron Microscopy (FESEM) spectroscopy. Such measured physical parameters like density and molar volume were found to vary linearly with increasing the CaO content in the bioglass composition. X-ray powder diffractrogram showed that the ASF bioglass samples with higher amount of CaO content are in amorphous phase, but a small and sharp peak crystal phase was observed and known as fluorapatite (Ca5(PO4)3F). Meanwhile, FTIR spectroscopy revealed various bonds such as Sisingle bondOsingle bondSi, Psingle bondOsingle bondP, Csingle bondO and Osingle bondH, indicated to the formation of ASF bioglass before sintering occurred. FESEM analysis showed non-uniform particle distribution, irregular in shape and random grain size of the bioglass. Although this type of bioglass is well established for dental application, its effect on waste materials such as CS and SLS for used in dental field has not been extensively studied. Revealed various bonds, stretching and bending vibrations within the samples before sintering occurred.